Researchers experience of using the regulatory affairs information system (RAIS) in strengthening research compliance in a large research program; A case study of the Infectious Diseases Institute(IDI) in Uganda - Nabukenya, Sylvia; Okoboi, Stephen; Nakate, Vivian; Twimukye, Adelline; Opio, Bruce; Castelnuovo, Barbara (JAMIA open, 2022)
The aim of this study was to explore researchers’ experience of using the regulatory affairs information system (RAIS) in strengthening research compliance to national ethics guidelines through tracking ethics and regulatory approvals for research projects at the Infectious Diseases Institute. We conducted a cross-sectional study using purposive sampling of 50 participants who were principal investigators (PI) and study coordinators (SC) of active projects between November 2019 and January 2020. Only 36 of them responded to the survey. We also conducted 12 key informant interviews among PI, SC, and research management at the Institute. We used STATA 13 to analyze responses to the survey. The interviews lasted between 20 and 30 min. We used NVivo 10 software to manage the transcripts and generation of themes. Majority 19 (52.8%) of those who participated in the survey were study coordinators, 19 (52.8%) had participated in more than 5 research studies, 28 (90.3%) had ever received a notification from the RAIS and 26 (92.9%) submitted requests for renewal of their studies approvals to Ethics committees and regulatory bodies 4 weeks prior to expiration dates. The study also examined participants’ general understanding of the regulatory requirements and all were aware that RECs and NDA grant approval for a period of 1 year, and 35 (97.2%) that UNCST grants approval for the duration of the study. Three prominent themes; researchers’ experiences, benefits, and shortcomings of RAIS were generated from the key informant interviews. Having experience in research coupled with a novel automated system provides a platform for a better understanding of research regulatory requirements, hence compliance to the national guidelines. Our case study demonstrates that supporting researchers and research institutions in low resource settings with an automated system in tracking expiration dates for research approvals can facilitate compliance to national ethics guidelines.
Keywords: Research program; Regulatory affairs information system (RAIS); Researchers